2012
DOI: 10.1016/j.jana.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators in Implementing “Prevention for Positives” Alcohol-Reduction Support: The Perspectives of Directors and Providers in Hospital-Based HIV Care Centers

Abstract: HIV-infected patients have considerable need for alcohol reduction support, and HIV care providers are strategically placed to implement a “prevention for positives” alcohol reduction approach through alcohol screening and brief interventions (SBIs). To facilitate this approach, we provided alcohol SBI education and training to HIV care providers in four hospital-based, New York City HIV Care Centers in 2007. Interviews with the medical directors and 14 of the HIV care providers who attended the training ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…This finding is supported by prior qualitative reviews of alcohol screening in clinic settings, which highlight the barriers to enhancing screening of patient alcohol use; trials on the efficacy of brief interventions for alcohol risk reduction are notable exceptions to this trend. 45, 48 HIV providers in our sample perceived a lack of patient receptivity and low readiness to change their alcohol behaviors. By contrast, among alcohol providers, their ambivalence may reflect a sense that HIV-associated interventions are beyond the scope of their care and not necessarily pertinent to their work.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This finding is supported by prior qualitative reviews of alcohol screening in clinic settings, which highlight the barriers to enhancing screening of patient alcohol use; trials on the efficacy of brief interventions for alcohol risk reduction are notable exceptions to this trend. 45, 48 HIV providers in our sample perceived a lack of patient receptivity and low readiness to change their alcohol behaviors. By contrast, among alcohol providers, their ambivalence may reflect a sense that HIV-associated interventions are beyond the scope of their care and not necessarily pertinent to their work.…”
Section: Discussionmentioning
confidence: 86%
“…47 The challenges in performing an effective assessment of alcohol use are compounded by the lack of time available in most clinical encounters to address these challenging issues. 48 In a study of HIV providers in New York, it was found that having a fixed case load, increased duration of time in practice, exposure to information on HIV and alcohol use, and perceived self-efficacy were important determinants for use alcohol interventions in practice. 49 There have been no studies addressing the role or the challenges of addressing HIV care in the context of alcohol treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the successful treatments took 6–15 sessions (9–22.5 hours) to achieve their results. Limited staff time and resources in HIV primary care clinics generally preclude such treatment within the clinic (Metsch et al, 2008; Strauss and Mino, 2011; Strauss et al, 2012, 2009) and patients seldom follow referrals from medical settings to outside alcohol treatment (Miller et al, 2006; Saitz, 2010). Thus, if briefer drinking-reduction interventions within the HIV medical setting were effective, they could provide an important means of helping HIV patients who drink heavily.…”
Section: Introductionmentioning
confidence: 99%
“…Not all providers educate drinkers about these risks (Strauss et al, 2009), consistent with findings of poor quality of HIV patient-provider communication among heavy drinkers compared to other groups of HIV patients (Korthuis et al, 2011). Educational discussions may not have occurred due to provider reservations about alcohol intervention (Strauss et al, 2009, Strauss et al, 2012), or patient under-reporting of drinking. Alternately, information may have been provided to the patients, but not understood or believed.…”
Section: Discussionmentioning
confidence: 99%
“…When providers do discuss drinking, their recommendations are variable, with some providers recommending abstention and others citing health benefits of moderate drinking (Shacham et al, 2011). Similar to other primary care settings, providers in HIV settings underutilize brief, effective drinking interventions due to skepticism regarding their efficacy, low concern about patients’ drinking, and time limitations (Strauss et al, 2012, Strauss et al, 2009). …”
Section: Introductionmentioning
confidence: 99%